142 FREQUENCY AND IMPACT OF PHYSICAL ACTIVITY COUNSELING IN PRESCHOOL CHILDREN. (1st January 2006) - Hare, M. E.; Somes, G. W.; Richey, P. A.; Shorr, R. I.; Klesges, L. M.
Abstract : Background: Despite the benefits of physical activity, overall engagement time in physical activity is low among American youth, even among preschool-aged children. Parental perceptions and attitudes may be influential in promoting physical activity in children. Objective: To assess parental receipt of physical activity health promotion counseling for their children and associations with perceptions and attitudes regarding physical activity and television viewing in their preschool children. Study Design: As part of an intervention to increase physical activity in a group of inner city, Title I, preschool children, a questionnaire regarding physical activity was completed by the preschooler's parent (or guardian). Questions assessed frequency of parental counseling by school or health provider, parental perception of activity level, time engaged in television viewing and eating dinner while watching television. Frequencies of responses were obtained for each question and chi-square analysis was used to assess the relationship between variables of interest. Results: 1, 178 parents were surveyed. 1, 100 (93%) completed part or all of the questionnaire. Overall 88% of respondents felt their child got about the right amount or too much physical activity. Children's TV/computer/video time was reported as $ 2 hours/day for 38% on weekdays and 57% on weekends while 62% of children ate dinner at least 2 times a week while watching television. Overall, only 22% of parents felt their child's TV/computer/video time was too much. The association between perceptions of the right amount of TV viewing and the hours of television viewed was significant (p < .0001). Most respondents reported never being counseled at school (50%) or by their health provider (63%), regarding their child's TV/computer/video time and 45% reported never having been counseled by school or health provider regarding their child's amount of physical activity. There was no significant association between parental receipt of counseling at school or health clinic and the amount of TV viewed or parental perceptions of the amount of their child's TV viewing time or physical activity. However, there was an association between counseling at the preschooler's health clinic and the child's hours of physical activity at home (p = .001). Conclusion: Many preschool parents do not receive counseling about the importance of physical activity and decreasing sedentary behaviors at their child's school or by health providers. Parental receipt of counseling at their child's health clinic but not school was related to their child's physical activity time. It was not related to children's sedentary behaviors or parent's perceptions about these behaviors.